Problems of Research of Cultural and Educational Activities of P.I.Kholodny in Historiography and Source Study - Teliachiy, Yuriy (Pedagogical Discourse, 2013)
The contribution of Kholodny Petrо Ivanovych (1876-1930) in the development of national education, science and culture is characterized in the article. The periodization of his creative career is concretized. The problems of studying his creative biography that exist in the national historiography and source study are disclosed. The priorities towards a fundamental comprehensive study on P. I. Kholodny by historians, educators, art critics are identified.